Physicochemical characterization of drinking water of selected regions in Bangladesh (Progressive Agriculture, 2020)
Water, the most vital resources for the survival of life is of major importance not only to have an adequate and accessible supply, but also to have quality water that is considered safe for human consumption. The study was designed with a view to investigating water quality by assessing physicochemical properties of drinking water collected from selected regions and to compare the regional variation among the quality of water. The analysed physical properties were pH, electrical conductivity (EC), total dissolved solids (TDS) and the chemical properties were Iron (Fe) Lead (Pb), Sulphate (SO42-) and Phosphate (PO43-). Water samples were collected from separate point of tap water and tube well water and most of them were collected from restaurant, house hold and governmental office within the study areas. The result revealed:(a) the highest value for physical parameters pH, EC and TDS were 7.8, 723 µs/cm and535 mg/L respectively whereas for chemical parameters SO42-, PO43- and Fe it was 1.6, 0.53 and 1.1 mg/L respectively; (b) the lowest value for pH, EC and TDS were 6.9, 430 µs/cm and 180 mg/L respectively whereas for SO42-, PO43- and Fe it was 0.05, 0.04 and 0.05 mg/L respectively. All of them were present in water within the permissible limits except Fe (1.1 mg/L) and TDS (535 mg/L) as it exceeds WHO standards (0.3-1 mg/L) for Fe and (500 mg/L) for TDS (WHO, 2012). The result obtained for experimental parameters indicates that the water quality is slightly harmful for drinking purposes in terms of (Fe) household and (TDS) govt. office in some regions.Progressive Agriculture 31 (1): 36-44, 2020